Integrated advertising, promotion, and marketing communications - Clow, Kenneth E. 4 0 16; Baack, Donald; 5 (Upper Saddle River, New Jersey : Pearson, 2010)
A comprehensive overview of integrated marketing communications that discusses corporate image and brand management, buyer behaviors, promotions opportunity analysis, advertising management, media channels, E-active marketing, regulations and ethical concerns, and other related topics.
Includes bibliographical references and indexes.
Adult.
Keywords: 2 -- 0; 6; Communication in marketing.;Advertising.;Communication.;Marketing.; 20; 2